CRIMINAL LIABILITY IN THE ACT OF THEFT (VIDE ARTICLE 362 KUHP) OF GOLD WHICH IS COMMITTED ON A CONTINUOUS BASIS (VOORTGEZETTE HANDELING VIDE ARTICLE 64 KUHP) - Adistyawan, Fany; Rubaie, Ach; Khoidin, M; Djaja, Dudik (Fakultas Hukum Universitas Padjadjaran, 2024)
Continuing actions are a combination of several actions committed by a person, where between one action and another action there has never been a judge's decision that has permanent legal force, so that the perpetrator is subject to a certain method of punishment, as stipulated in article 64 of the Criminal Code. This combined form in Dutch is known as